Influences of traditional Japanese literature on selected works of Oe Kenzaburo - Macatangay, Ma. Leilani C. (Animo Repository, 1997)
This thesis studies how the works of Oe Kenzaburo show the influence of traditional Japanese literature. The thesis uses a historical survey of Japanese literature for its theoretical framework. The study presents two questions. The first question is, How Oe's works show the influence of traditional Japanese literature? The answer to this question is that Oe follows the conventions of writing common to all traditional Japanese literature. These conventions are -- the focus on the emotion, the use of the concrete, and the zuihitsu way of narration. The second question that this study presents is, Which aspects of Oe's works can be categorized as traditional and which are modern? The answer to this question is that the modern aspect of Oe's works is the confrontative attitude he shows in his choice of subject matter. Oe presents the outcasts of Japanese society. The traditional aspect of his work is seen in the fact that he uses traditional conventions to present his modern themes.